Dietary supplements for football - Hespel, P.; Maughan, R. J.; Greenhaff, P. L. (Journal of Sports Sciences, 2006)
Physical training and competition in football markedly increase the need for macro- and micronutrient intake. This requirement can generally be met by dietary management without the need for dietary supplemens. In fact, the efficacy of most supplements available on the market is unproven. In addition, players must be cautious of inadequate product labelling and supplement impurities that may cause a positive drug test. Nonetheless, a number of dietary supplements may beneficially affect football performance. A high endurance capacity is a prerequisite for optimal match performance, particularly if extra time is played. In this context, the potential of low-dose caffeine ingestion (2 - 5 mg · kg body mass-1) to enhance endurance performance is well established. However, in the case of football, care must be taken not to overdose because visual information processing might be impaired. Scoring and preventing goals as a rule requires production of high power output. Dietary creatine supplementation (loading dose: 15 - 20 g · day-1, 4 - 5 days; maintenance dose: 2 - 5 g g · day-1) has been found to increase muscle power output, especially during intermittent sprint exercises. Furthermore, creatine intake can augment muscle adaptations to resistance training. Team success and performance also depend on player availability, and thus injury prevention and health maintenance. Glucosamine or chondroitin may be useful in the treatment of joint pain and osteoarthritis, but there is no evidence to support the view that the administration of these supplements will be preventative. Ephedra-containing weight-loss cocktails should certainly be avoided due to reported adverse health effects and positive doping outcomes. Finally, the efficacy of antioxidant or vitamin C intake in excess of the normal recommended dietary dose is equivocal. Responses to dietary supplements can vary substantially between individuals, and therefore the ingestion of any supplement must be assessed in training before being used in competition. It is recommended that dietary supplements are only used based on the advice of a qualified sports nutrition professional.